A Bibliometric Analysis of Artificial Intelligence during COVID-19 Based on WOS Data Abdelmageed Algamdi - Algamdi, Abdelmageed (Finance and Business Economies Review, 2022)
This article opens up a new field of research in Light of COVID-19 Artificial Intelligence, mainly explaining this binding domain's current trends and knowledge fields. The bibliometric analysis was performed to present new research trends in Artificial Intelligence in light of COVID-19. The data of 1635 studies published in Web of Science were analyzed during the last two years (2020-2021) using three software CiteSpace, VOSviewer, and KnowledgeMatrix Plus. The findings suggest that there are twelve research clusters in this topic (emerging industry, cross-sectional survey study, emerging technologies, joint position paper, colony predation algorithm, medical worker, deep learning, covid-19 risk prediction, future smart connected communities, supply chain resilience, virtual screening, and k-12 students). The United States, People's Republic of China, the United Kingdom, India, Saudi Arabia, Italy, Australia, Spain, South Korea, and Canada are the most intriguing countries that investigated this issue during COVID-19, so this study reveals the latest policy trends in Artificial intelligence using bibliometric analysis